Balancing Medical Knowledge with Behavioral Strategies: Content Characteristics of High-Performing Pediatric Diabetes Videos on Indonesian TikTok - Rahayu, Agustin Putri; Rahayu, Eka Putri; Ariyanti, Rea (Universitas Mulawarman, 2025)
Pediatric diabetes has become rapidly growing, with epidemiological projections indicating that nearly half of children with type 1 diabetes remained undiagnosed globally, while type 2 diabetes prevalence among youth increased more markedly than type 1 diabetes in several regions. This research aimed to conduct a comprehensive content analysis of the fifteen most highly engaged pediatric diabetes educational videos on TikTok within the Indonesian digital landscape over the past six months. The research method employed a quantitative content analysis design conducted on May 28, 2025, analyzing TikTok content using the keyword